(untitled) (International Seven Journal of Multidisciplinary, 2021)
Generalized Anxiety Disorder (GAD) is a prevalent and debilitating mental health condition characterized by chronic, excessive worry across multiple domains of life. Due to the substantial symptomatic overlap with other psychiatric disorders—such as major depressive disorder, panic disorder, and social anxiety disorder—accurate differential diagnosis is essential. This paper examines the diagnostic criteria established by the DSM-5-TR and explores how GAD can be reliably distinguished from similar conditions. Evidence-based treatment protocols are reviewed in depth, with a focus on the efficacy of cognitive behavioral therapy (CBT), selective serotonin reuptake inhibitors (SSRIs), and newer interventions rooted in affective neuroscience, including mindfulness-based strategies and emotion regulation techniques. Additional attention is given to emerging digital therapies, biological markers, cultural considerations, and integrated care models. The review concludes by emphasizing the need for individualized, culturally sensitive, and multidisciplinary approaches to the treatment of GAD, based on the latest empirical findings.